Pengembangan literasi matematika pada aspek pembiasaan dan pembelajaran bagi guru sekolah dasar dikecamatan girimarto kabupaten wonogiri - Riyadi Riyadi; Anesa Surya; Sandra Bayu Kurniawan (Universitas Sebelas Maret, 2022)
Literacy is one of the elements assessed in PISA. The research objective was to determine the mathematics literacy skills of elementary school teachers and the development of mathematics literacy in primary schools. This research activity consists of 3 stages, namely the pre-training stage, the implementation stage and the program evaluation stage. Activities carried out in the pre-training stage are need analysis and preparing training instruments. The program implementation activities consist of 3 stages, namely 1) Expert explanation on mathematical literacy 2) Planning and compilation of habituation and learning that can develop mathematical literacy 3) Providing feedback on the development of mathematical literacy through the peer-correction stage. Activities carried out in program evaluation include mentoring the application of habituation and learning that can develop elementary school students' mathematical literacy. Based on the results of statistical tests, it is concluded that the Mathematical Literacy Development Workshop on the Aspects of Habit and Learning for Elementary School Teachers can improve the understanding of workshop participants. The understanding of elementary school teachers in Wonogiri district has increased compared to before the training activities were implemented. This means that community service activities are useful for elementary school teachers in Wonogiri district. These results are also with the results of interviews and teacher assessment questionnaires that the Mathematical Literacy Development Workshop on the Aspects of Habitual and Learning for Elementary School Teachers is very useful for elementary school teachers in improving their pedagogical abilities.